A glimpse inside the Banarasi mind: What do linguistic categories reveal about Banarasi toys?. Issue 2 (1st October 2014) - Patil, Koumudi
This study focuses on the design of Banarasi Khilona, which are wooden lacquer toys from Banaras, India. The study presents a category-based approach to elucidate how these craft-based artefacts are designed for acceptability and for novelty. For this purpose, the study traces the community perceptions of Banarasi Khilona by examining the expression of linguistic categories that both shape and are shaped by the Khilona. This vocabulary, which reflects how Banarasi people structure their world, suggests a system of categorization in which objects have multiple ways of being categorized. It further suggests that it is at the community-acceptable common intersection point of multiple categories that the Banarasi craftspersons produce a Khilona. This study shows that although the community-acceptable combinations of multiple categories appear fixed, they are yet open to deviant members in the fuzzy boundary of the categories where the hold of myths, taboos and traditions is relatively weaker. Thus there is a potential space for occurrence and sometimes acceptance of deviant members in an otherwise tradition-bound craft practice.Understanding artefacts through and between categories, instead of studying them in isolation of their natural groupings, facilitates their decoding as acceptable/unacceptable or typical/untypical rather than conventional/new or traditional/innovative. Distinctions of acceptability and typicality have the potential to inform design decisions of culturally relevant artefacts in a globalized context.